The long-term perspective of human impact on landscape for environmental change and sustainability - Mercuri, Anna Maria 1961-; Florenzano, Assunta (MDPI, 2019)
The research studies included in this Special Issue highlight the fundamental contribution of the knowledge of environmental history to conscious and efficient environment conservation and management. The long-term perspective of the dynamics that govern the human-climate ecosystem is becoming one of the main focuses of interest in biological and earth system sciences. Multidisciplinary bio-geo-archaeo investigations into the underlying processes of human impact on the landscape are crucial to envisage possible future scenarios of biosphere responses to global warming and biodiversity losses. This Special Issue seeks to engage an interdisciplinary dialog on the dynamic interactions between nature and society, focusing on long-term environmental data as an essential tool for better-informed landscape management decisions to achieve an equilibrium between conservation and sustainable resource exploitation
This is a reprint of articles from the special issue published online in the open access journal Sustainability
Keywords: Science (General); Environmental sciences